2017
DOI: 10.1089/lgbt.2016.0097
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sexual Orientation Identity on Medical Morbidities in Male-to-Female Transgender Patients

Abstract: Purpose: We aim to describe the relationship between sexual orientation identity and medical morbidities in a large sample of male-to-female (MTF) transgender patients. Methods: We reviewed medical records of patients presenting for MTF sex reassignment surgery (SRS) by a single, high-volume surgeon from 2011 to 2015. Sexual attraction to men (heterosexual), women (lesbian), or both (bisexual) was asked of each patient. We examined 16 medical morbidities for this analysis. Results: During the study period, 330… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…We demonstrated, for example, that our patients were more frequently sexually attracted to women or bisexual, if they belonged to the older cohort (Table 3). These findings are consistent with those of Gaither et al, 24 who reported that gynephilic MtFs presenting for GAS were significantly older than heterosexual or bisexual controls. A study reporting on a consecutive series of predominantly young MtF patients in Spain with a mean age of 29.4 years at their day of surgery showed that 89.9% were sexually interested in men 27 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We demonstrated, for example, that our patients were more frequently sexually attracted to women or bisexual, if they belonged to the older cohort (Table 3). These findings are consistent with those of Gaither et al, 24 who reported that gynephilic MtFs presenting for GAS were significantly older than heterosexual or bisexual controls. A study reporting on a consecutive series of predominantly young MtF patients in Spain with a mean age of 29.4 years at their day of surgery showed that 89.9% were sexually interested in men 27 .…”
Section: Discussionsupporting
confidence: 92%
“…Advocates of this 2-population model suggest that the 2 groups can be further distinguished on demographic criteria and clinical presentation 9, 23. Those who endorse this taxonomy have suggested, for example, that androphilic MtF individuals generally seek GAS earlier than those in the gynephilia group 24 . They have also suggested that individuals in the androphilic group are less likely to have a history of being married to women and to have fathered children.…”
Section: Discussionmentioning
confidence: 99%
“…13 Medical comorbidities, such as HIV or depression, may differ among transgender women who identify as straight, lesbian, or bisexual. 14 Measurement of sexual orientation in this population is complicated for many reasons, however, not the least of which is the contingency of common labels for sexual orientation on the subject's own gender. Identities may change over timethe relationship between development of gender and sexual orientation identities are complex, interrelated, and not fully understood but evidence suggests that gender-affirming care may alter individuals' perceptions of their own sexuality.…”
Section: Introductionmentioning
confidence: 99%
“…Transgender adults and adolescents endorse multiple sexual orientation identities to describe attraction across gender lines. [32][33][34][35][36] As such, accurate assessment of transgender individuals' sexual health requires an understanding of both their sexual orientation and gender identity, the sexual behaviors in which they are engaging, and the people with whom they are having sex. However, information on how to take routine sexual histories of transgender patients is sparse.…”
Section: Introductionmentioning
confidence: 99%